SISTEM PENGENDALIAN INTERN PENGADAAN BARANG PADA PT. BUDI BAKTI SAMARINDA - Tiowati, Eries Sulis (EKONOMIA, 2016)
Eries Sulis Tiowati, Faculty of Economics, University of Samarinda August 17, 1945, "Internal Control System Procurement at PT. Budi Bakti Samarinda", led by Mr. LCA.Robin Jonathan and Mr. Adi Suroso.The success of a company is only Able to Be Achieved with good management, the which is capable of sustaining kontunuitas management company by gaining maximum profit in accordance with the company's goals in general. In the field of construction procurement is a project with a range of abuses, so here the company conducts internal controls in order to gain efficiency and effectiveness.Research conducted on procurement internal control at PT. Budi Bakti Samarinda, using questionnaires to the COSO internal control framework Refers to an element - an element of internal control. The test results Showed that of the element - the element of internal control in accordance with the COSO framework, the elements of the control environment, risk determination, control activities, information and communication and monitoring is not effective.